2020
DOI: 10.3329/bjid.v7i00.50159
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge and Practices Regarding Prevention and Control of COVID-19 Infection in a Tertiary Level Hospital

Abstract: Background: Bangladesh is a highly populated country for that reasonCOVID-19 is highly transmittable infection in Bangladesh. Objective: The aim of this study was to identify the nurses’ knowledge and practices regarding prevention and control of COVID-19 infection. Methodology: This cross-sectional study was conducted in Rajshahi Medical College Hospital, Rajshahi, Bangladesh from April to July 2020. The questionnaires were completed and returned by the nurses. Collected data were checked, coded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…Based on the results of the literature search found 21 articles (Table 1) generally assessed the knowledge, attitudes, practices, perceptions, anxiety, and psychological responses of nurses related to COVID-19. Four articles were found in China (Chen et al, 2020;Huang et al, 2020;Jin & Yi, 2020;Li et al, 2020), two in Arabian (Al-Dossary et al, 2020;Alreshidi, 2020), two in India (Adhikari et al, 2020;Patidar et al, 2020), one in Nepal (Kafle et al, 2020), three in Turkey (Aydin & Balci, 2020;Gumus & Basgun, 2020;Semerci et al,2020), one in Northern Ethiopia (Tadesse et al, 2020), two in Pakistan (Alwani et al, 2020;Zafar et al, 2020), one in Iran (Nemati et al, 2020), one in Lebanon (Saadeh et al,2020), one in Ghana (Buertey et al, 2020), one in Indonesia (Sahar et al, 2020), one in Bangladesh (Saha, et al, 2020), and one in Egypt (Goda Elbqry, 2020). The number of samples between 85-1.323 nurses, using a questionnaire as an instrument, the study used a cross-sectional study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of the literature search found 21 articles (Table 1) generally assessed the knowledge, attitudes, practices, perceptions, anxiety, and psychological responses of nurses related to COVID-19. Four articles were found in China (Chen et al, 2020;Huang et al, 2020;Jin & Yi, 2020;Li et al, 2020), two in Arabian (Al-Dossary et al, 2020;Alreshidi, 2020), two in India (Adhikari et al, 2020;Patidar et al, 2020), one in Nepal (Kafle et al, 2020), three in Turkey (Aydin & Balci, 2020;Gumus & Basgun, 2020;Semerci et al,2020), one in Northern Ethiopia (Tadesse et al, 2020), two in Pakistan (Alwani et al, 2020;Zafar et al, 2020), one in Iran (Nemati et al, 2020), one in Lebanon (Saadeh et al,2020), one in Ghana (Buertey et al, 2020), one in Indonesia (Sahar et al, 2020), one in Bangladesh (Saha, et al, 2020), and one in Egypt (Goda Elbqry, 2020). The number of samples between 85-1.323 nurses, using a questionnaire as an instrument, the study used a cross-sectional study.…”
Section: Resultsmentioning
confidence: 99%
“…Research in Indonesia, of 368 PHN nurses, nurses had good practices related to COVID-19, factors related to practice were gender, and resources (Sahar et al, 2020). Research in Bangladesh, 73.42% of nurses have good practice, 21.84% moderate practice, and 8.68% bad practice, there is a significant relationship between knowledge and practice of nurses (Saha et al, 2020). Research in Egypt, findings showed that the nurses studied had satisfactory practices related to COVID-19 (Goda Elbqry, 2020).…”
Section: Practice Related To Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The current study results regarding item analysis were quite similar with the previous study of Egypt, India, and Nepal. [30][31][32] The findings might be due to as anew emerging disease, sign and symptoms, mode of transmission, prevention and management of this fatal disease has not yet been identified. Treatment guidelines or nursing management has not been developed.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in Bangladesh hospitals showed that nearly two-thirds percent of nurses (73.42%) held good knowledge and 73.42% of nurses had good practices towards prevention and control of COVID-19 infection 18,19 . As future healthcare providers, nursing students need to make themselves mentally strong by offering quality training and teaching that will affect the outcomes and will help them to take upcoming courageous steps.…”
mentioning
confidence: 99%